THE ROLE OF FORENSIC LABORATORIES IN PROVING POISON MURDERS IN INDONESIA - Astrya Puspitasari; Diya Ul Akmal (Universitas Muhammadiyah Tangerang, 2022)
Murder is a heinous crime that violates the law and threatens humanity. Murder can be committed in a variety of ways, one of which is through the use of poison. To solve a Poisoning Murder case, investigators must have a high level of expertise as well as the use of a Forensic Laboratory to examine scientific evidence. The murder of Wayan Mirna Salihin (Mirna) with Cyanide is one example. This study uses a Normative Legal Method that is bolstered by primary data analysis. The data used are Primary Data (Interviews) and Secondary Data (Legislation, Books, Journals, and Internet Sources). The obtained data is described using words based on scientific logic. The Mirna Cyanide murder case is so complicated that it necessitates the involvement of the Forensic Laboratory and forensic experts from various fields. Expert Testimony from Forensic Doctors, Forensic Toxicologists, and Forensic Digital Experts were obtained as part of the evidence. In this case, Expert Testimony is crucial in confirming the judge's conviction of the suspect who murdered Mirna. Jessica Kumala Wongso (Jessica) was eventually found guilty and sentenced to 20 years in prison by the judge. This emphasizes the importance of the Forensic Laboratory in proving Poison Murder cases.